2012
DOI: 10.1371/journal.pone.0034955
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Structure of the Tree Peony (Paeonia rockii) and the Qinling Mountains as a Geographic Barrier Driving the Fragmentation of a Large Population

Abstract: BackgroundTree peonies are great ornamental plants associated with a rich ethnobotanical history in Chinese culture and have recently been used as an evolutionary model. The Qinling Mountains represent a significant geographic barrier in Asia, dividing mainland China into northern (temperate) and southern (semi–tropical) regions; however, their flora has not been well analyzed. In this study, the genetic differentiation and genetic structure of Paeonia rockii and the role of the Qinling Mountains as a barrier … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
83
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 67 publications
(95 citation statements)
references
References 48 publications
10
83
2
Order By: Relevance
“…Some refugia proposed by this study (Fig. 2c) are corroborated by other case studies; for example, the WQM, MQM, and FNM were considered as refugia for the tree peony (Paeonia rockii) (Yuan et al 2012), the WQM was a refugium for the Chinese Hwamei (Leucodioptron canorum canorum) , and the WQM, MQM, and EQM were refugia for the Gray-cheeked Fulvetta (Alcippe morrisonia) during the Pleistocene ice ages (Song et al 2009). Certainly, we need more cases to make generalizations about the genetic and demographic legacies of the glacial oscillations on organisms in this region.…”
Section: Prolonged Divergence and Multiple Glacial Refugiasupporting
confidence: 85%
“…Some refugia proposed by this study (Fig. 2c) are corroborated by other case studies; for example, the WQM, MQM, and FNM were considered as refugia for the tree peony (Paeonia rockii) (Yuan et al 2012), the WQM was a refugium for the Chinese Hwamei (Leucodioptron canorum canorum) , and the WQM, MQM, and EQM were refugia for the Gray-cheeked Fulvetta (Alcippe morrisonia) during the Pleistocene ice ages (Song et al 2009). Certainly, we need more cases to make generalizations about the genetic and demographic legacies of the glacial oscillations on organisms in this region.…”
Section: Prolonged Divergence and Multiple Glacial Refugiasupporting
confidence: 85%
“…Mitochondrial DNA analysis revealed the same spatial pattern, which suggested that they might come from different refugia in the Qinling area (Chen et al, 2008;unpublished data). Interestingly, populations of Paeonia rochii in the Qinling Mountains can also be grouped into eastern and western Qinling genetic clusters (Yuan et al, 2012). Plant populations in this area probably have experienced a common history with past fragmentation of a large population and low dispersal rates.…”
Section: Spatial Structure and Geographic Barriersmentioning
confidence: 98%
“…Simple-sequence repeat (SSR) markers are powerful tools for investigating the population genetics of wild species (Yuan et al, 2012;Zhai et al, 2012). Within the genus Prunus, numerous SSR markers have been developed, including markers for peach (Cipriani et al, 1999;Testolin et al, 2000;Dirlewanger et al, 2002), cherry (Downey and Iezzoni, 2000;Struss et al, 2003), and Japanese plum (Mnejja et al, 2004), and are transferable between species for genetic diversity analyses (Downey and Iezzoni, 2000;Dirlewanger et al, 2002).…”
Section: Introductionmentioning
confidence: 99%